Implementation of Multicultural Education Values In History Learning at SMA NEGERI Siwalima Ambon - Rianko Luturmas (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Multicultural education is an educational concept that recognizes differences / diversity in a frame of togetherness and equality. The concept of multicultural education is relevant in the concept of a country that has cultural diversity like Indonesia. Education is one of the effective media to develop multiculturalist awareness. Educational curriculum development must be based on the socio-cultural context of the community. So it must be realized that historical learning has a big role in the development of multicultural education, considering that historical pursuits present various historical facts of the nation which of course have a diversity of identities and cultures. Through identification of historical material contained in the syllabus of history subjects in schools, it is found that some content is loaded with the development of multicultural values.